'My Flesh is Food Indeed': Eckhart and Aquinas on the Body of Christ. Issue 2 (25th November 2013) - Michael Demkovich, OP
Abstract : The papal bull, In agro dominico, article 10, condemns a key concept in Eckhart's 'Eucharistic Theology' as containing 'the error or stain of heresy'. On closer examination we see that the bull misrepresents Eckhart's position and diminishes the Eucharist. Eckhart clearly has grounded his position in Aquinas, but has also developed it in light of his own notion of deiformitas ( gottesgeburt ), our transformation into the Body of Christ.